Ambulantno predpisovanje antihipetenzivov in kakovost nadzora arterijske hipertenzije v Sloveniji - Korpar, Marjetka (visokošolska dela, 2014)
Despite nurnerous interventions, arterial hypertension (AH) remains one of the mostimportantrisk factors of cardiovascular diseases in developed countries. The number of published epidemiological studies on prevalence and quality of AH control and AH clinical consequences is large worldwide. However, in Slovenia there are only few such large epidemiological studies. Family medicine (general practice) physicians have the central role in AH management in Slovenia, therefore in our study we evaluated the quality of AH control in family practice. The data were gained from the "Quality of Healthcare in Slovenia" project.The final sample included 18,260 patients, visiting their family medicine physicians. According to the recommended guidelines the control blood pressure goals were < 140mmHg for systolic blood pressure (SBP) and < 90 mmHg for diastolic blood pressure (DBP). We found out that the AH control was relatively high (55.8%) in the whole studied population in the period 2002-2008, also when compared to other European countries and to previous Slovene studies, in which more than 50% control was rarely reported. Various factors may contribute to high AH control in our study: guidelines' implementation, frequent educational programs for physicians and other medical workers, greater patients' awareness, introduction of quality control in Slovene healthcare system, and others. Among other factors, adequate AH control depends also on appropriate pharmacological treatment. Patients diagnosed with AH often have other chronic diseases and consume number of drugs,leading to drug related problems, including undesirable drug interactions. Therefore, int he second part of this dissertation, we evaluated the number of potential drug interactions with antihypertensives among 453,871 patients, who had received an antihypertensive drug at least once in year 2010. The data were obtained from the Health Insurance Institute of Slovenia from the database of drugs dispensed in 2010 by all Slovene community pharmacies. Potential drug interaction pairs were identified by three sources: Stockley's Drug Interactions books and two on-line databases, Lexi-Interact (payable) and Drug lnteraction Checker (DIC, free access). 1.561 drug interacting pairs were identified, which are contraindicated or potentially harmful and dosage adjustment or close patient's monitoring is needed, when concomitantly used. Contraindicated pairs of drugs were dispensed in 16,315 and in 1,010 cases in +/- 30 days interval according to Lexi-Interact (type X) and Stockley, respectively.The most widely dispensed contraindicated drug combinations were: (i) nonspecific beta-adrenoceptor antagonist and beta2 adrenoceptor agonist, (ii) two alpha-adrenoceptor antagonists, (iii) indapamide and quetiapine, (iv) verapamil or diltiazem with amiodarone, (v) nimodipine and carbamazepine, (vi) aliskiren and verapamil and (vii) lercanidipine and cyclosporine. The frequency of potential drug interactions according to the therapeutic subgroup (based on Anatomical-Therapeutic-Chemical Classification (ATC)) was similar for the same day and +/-30 day dispension interval and declined as follows: diuretics (C03), drugs acting on renin-angiotensin system (C09), beta-adrenoceptor antagonists (C07), voltage-dependent calcium channel blockers (C08) and antihypertensives (C02). Results of our study may contribute to the insight of AH control in family medicine practice and evaluation of potential drug interactions of antihypertensives with other concomitantly prescribed drugs in primary care in Slovenia. Despite some study limitations, we may conclude that AH control in Slovenia is high and comparable to other European countries. Identified potential drug interactions need to be carefully interpreted as the majority of these interactions is not clinically expressed. However, our results represent a valuable review of frequency of potential drug interactions with antihypertensives and as such a valuable basis for future improvements and studies, such as: examinations of medical records of patients, who were prescribed studied drug combination and their clinical picture monitoring, especially when drug-related problems are possible.
Keywords: ambulantno predpisovanje; Antihipertenzivi; Arterijska hipertenzija; Disertacije; Družinska medicina; farmakoterapija; Interakcije; Nadzor; zdravila